The bacterial and pathogenic landscape of African buffalo (Syncerus caffer) whole blood and serum from Kenya - Nyamota, Richard; Middlebrook, E.A.; Abkallo, Hussein M.; Akoko, James M.; Gakuya, F.; Wambua, Lillian; Ronoh, B.; Lekolool, I.; Mwatondo, Athman; Muturi, Mathew; Bett, Bernard K.; Fair, J.M.; et al. (BioMed Central, 2025)
Background: African buffalo (Syncerus caffer) is a significant reservoir host for many zoonotic and parasitic infections in Africa. These include a range of viruses and pathogenic bacteria, such as tick-borne rickettsial organisms. Despite the considerations of mammalian blood as a sterile environment, blood microbiome sequencing could become crucial for agnostic biosurveillance. This study investigated the blood microbiome of clinically healthy wild buffaloes in Kenya to determine its applicability in agnostic testing for bacteria in apparently healthy wild animals.